Segmental Colectomy for Ulcerative Colitis: Is There a Place in Selected Patients Without Active Colitis? An International Multicentric Retrospective Study in 72 Patients. (4th June 2020) - Frontali, A; Cohen, L; Bridoux, V; Myrelid, P; Sica, G; Poggioli, Gilberto; Espin, E; Beyer-Berjot, L; Laharie, D; Spinelli, A; Zerbib, P; Sampietro, G; et al.
Abstract: Background and Aims: The aim of this study was to report a multicentric experience of segmental colectomy [SC] in ulcerative colitis [UC] patients without active colitis, in order to assess if SC can or cannot represent an alternative to ileal pouch-anal anastomosis [IPAA]. Methods: All UC patients undergoing SC were included. Postoperative complications according to ClavienDindo's classification, long term results, and risk factors for postoperative colitis and reoperation for colitis on the remnant colon, were assessed. Results: A total of: 72 UC patients underwent: sigmoidectomy [ n = 28], right colectomy [ n = 24], proctectomy [ n = 11], or left colectomy [ n = 9] for colonic cancer [ n = 27], 'diverticulitis' [ n = 17], colonic stenosis [ n = 5], dysplasia or polyps [ n = 8], and miscellaneous [ n = 15]. Three patients died postoperatively and 5/69 patients [7%] developed early flare of UC within 3 months after SC. After a median followup of 40 months, 24/69 patients [35%] were reoperated after a median delay after SC of 19 months [range, 2–158 months]: 22/24 [92%] underwent total colectomy and ileorectal anastomosis [ n = 9] or total coloproctectomy [TCP] [ n = 13] and 2/24 [8%] an additional SC. Reasons for reoperation were: colitis [ n = 14; 20%], cancer [ n = 3] or dysplasia [ n = 3], colonic stenosis [ n = 1], and unknown reasons [ n = 3]. Endoscopic score of colitis before SC was Mayo 23 in 5/5 [100%] patients with early flare vs 15/42 without early flare [36%; p = 0.0101] and in 9/12 [75%] patients with reoperation for colitis vs 11/35 without reoperation [31%; p = 0.016]. Conclusions: After segmental colectomy in UC patients, postoperative early colitis is rare [7%]. Segmental colectomy could possibly represent an alternative to IPAA in selected UC patients without active colitis.